Association between parental emotional symptoms and child antisocial behaviour: What is specific and is it mediated by parenting?. (January 2015) - Hautmann, Christopher; Eichelberger, Ilka; Hanisch, Charlotte; Plück, Julia; Walter, Daniel; Döpfner, Manfred
Parental anxiety and depression are associated with antisocial behaviour of children. Several mechanisms may mediate this association. The aim of this study was to test whether parenting is a mediator of the association of parental anxiety and depression with the antisocial social behaviour of preschool children. The analysis was based on cross-sectional data and 106 German families of children with elevated externalizing behaviour problems were considered. Mothers and fathers were analysed separately. Depression and anxiety in parents were both associated with children's antisocial behaviour and this association was mediated by parenting. Further, our results indicated that the association between maternal depression and child behaviour is maintained after controlling for maternal anxiety, and that parenting of mothers is more strongly associated with child behaviour than parenting of fathers.